Przez okno świadomości : gatunki mowy w świadomości użytkowników języka - Zaśko-Zielińska, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2002)
The book refers both to linguistics and the theory of literature. The two areas are united by the names of M. Bachtin - the creator of the notion of genre of speech, so important for modern linguistics - and S. Skwarczyńska - the author of Próba teorii rozmowy (The Attempt at the Theory of Conversation) and her own genological concept, which included such notions as the awareness of genres and the life of genres. The work Through the Window of Awareness presents the method of researching linguistic awareness at the level of the genre of speech and the information concerning the results of such research. Questionnaires and analyses of metalanguage comments in the press ("Gazeta Wyborcza", "Rzeczpospolita", "Polityka", "Gość Niedzielny" and "Tygodnik Powszechny" from 1995-98) were the basis for the description of the awareness of genres on the part of the users of the language, which comprises: awareness of genological changes, knowledge of the communication situation, structure of genres of speech and their linguistic components and the possibilities of classifying genres of speech. Detailed analyses are concerned with the presence of metatext in editorials, with a review and its genre standard as well as with the description of genres in dictionaries. The work may support the development of awareness of genres, which is a method of improving linguistic efficiency of the contemporary people, who in their lifetimes may witness and initiate a much greater number of various communication situations than it was possible in the past.
Keywords: communication; linguistic awareness; literary types and genres